Brightening of dark excitons in monolayers of semiconducting transition metal dichalcogenides - Molas, M R; Faugeras, C; Slobodeniuk, A O; Nogajewski, K; Bartos, M; Basko, D M; Potemski, M (2d materials, 2017)
We present low-temperature magneto-photoluminescence experiments which demonstrate the brightening of dark excitons by an in-plane magnetic field B applied to monolayers of different semiconducting transition metal dichalcogenides. For WSe2 and WS2 monolayers, the dark exciton emission is observed at   50 meV below the bright exciton peak and displays a characteristic doublet structure whose intensity grows with B2, while no magnetic field induced emission peaks appear for MoSe2 monolayer. Our experiments also show that the MoS2 monolayer has a dark exciton ground state with a dark-bright exciton splitting energy of   100 meV.